Comparison of the Effect of Two Purification Methods on the Immunogenicity of Recombinant Outer Membrane Protein H of Pasteurella multocida Serovar A:1 - Arunee Thanasarasakulpong; Pichayanut Poolperm; Weerapongse Tangjitjaroen; Thanya Varinrak; Takuo Sawada; Dirk Pfeiffer; Nattawooti Sthitmatee (Veterinary Medicine International)
Recombinant outer membrane protein H (rOmpH) of Pasteurella multocida strain X-73 can be purified using affinity chromatography but this adversely affects its immunogenicity. The current study presents the results from an intervention study comparing the immunogenicity of rOmpH purified using electroelution with rOmpH purified using affinity chromatography and native OmpH purified using electroelution and a nonimmunized control group. Chickens immunized with rOmpH purified using electroelution produced the highest ELISA antibody levels against P. multocida strains. Chickens in each of the 5 treatment groups were split into two subgroups for challenge with two different P. multocida strains. The average number of adhesions to CEF cells was statistically significantly lower in sera from chickens immunized with rOmpH or native OmpH purified using electroelution than in those of the three other treatment groups. The survival amongst chickens immunized with rOmpH or native OmpH purified using electroelution indicated high levels of protection. In contrast, survival probability was zero or low in the groups immunized with rOmpH purified using affinity chromatography and in the nonimmunized group. These findings show that the rOmpH purified using electroelution retains its immunogenicity and stimulates high levels of protection in chickens against P. multocida infection.